(WITHDRAWN) TASTING THROUGH THE LENS: THE ROLE OF FOOD PORN IN PROMOTING AUTHENTIC ASSAMESE CULTURAL EXPERIENCES FOR TOURISTS - . (ShodhKosh: Journal of Visual and Performing Arts, 2024)
(Withdrawn) The publisher made the decision to withdraw the article.